Mapping the anatomy of perceptual pseudoneglect. A multivariate approach - Jiaqing Chen; Andy C.H. Lee; Edward B. O’Neil; Mura Abdul-Nabi; Matthias Niemeier (NeuroImage, 2020)
Fundamental to the understanding of the functions of spatial cognition and attention is to clarify the underlying neural mechanisms. It is clear that relatively right-dominant activity in ventral and dorsal parieto-frontal cortex is associated with attentional reorienting, certain forms of mental imagery and spatial working memory for higher loads, while lesions mostly to right ventral areas cause spatial neglect with pathological attentional biases to the right side. In contrast, complementary leftward biases in healthy people, called pseudoneglect, have been associated with varying patterns of cortical activity. Notably, this inconsistency may be explained, at least in part, by the fact that pseudoneglect studies have often employed experimental paradigms that do not control sufficiently for cognitive processes unrelated to pseudoneglect. To address this issue, here we administered a carefully designed continuum of pseudoneglect and control tasks in healthy adults while using functional magnetic resonance imaging (fMRI). Data submitted to partial least square (PLS) imaging analysis yielded a significant latent variable that identified a right-dominant network of brain regions along the intra-occipital and -parietal sulci, frontal eye fields and right ventral cortex in association with perceptual pseudoneglect. Our results shed new light on the interplay of attentional and cognitive systems in pseudoneglect.